PENGARUH MODEL COOPERATIVE LEARNING TIPE TWO STAY TWO STRAY TERHADAP KEMAMPUAN MENGANALISIS SEJARAH SISWA DI SMA NEGERI 1 TEGINENENG - Mita Anjarwati; Bobi Hidayat (Swarnadwipa, 2018)
There are still many students who have not complete the ability to analyze the history of class X IPA SMA Negeri 1 Tegineneng academic year 2017/2018 and the purpose of this study is to be able to know the ability to analyze the history of students after the use of Cooperative Learning Model Type Two Stay Two Stray in class X IPA even semester SMA Negeri 1 Tegineneng Lesson Year 2017/2018. This research uses quasi experimental research type, while the design or research design used in this research is Nonequivalent control group design. Population in this research is all students of class X IPA even semester SMA Negeri 1 Tegineneng, research use sampling method clusterrondom sampling. So, in this study the researchers chose the class randomly in sampling. Class X IPA 1 as test class, class X IPA 2 as control class and class X IPA 3 as experiment class. There is influence of the use of cooperative learning model type two stay two stray to the ability to analyze history of class X student IPA even semester SMA Negeri 1 Tegineneng. Based on the results of analysis in the study the use of cooperative learning model type two stay two stray against the ability to analyze the history of students, it is concluded that cooperative learning model type two stay two stray positively affect the ability to analyze student history.